WiFi-NC : WiFi Over Narrow Channels - Chintalapudi, Krishna; Radunovic, Bozidar; Balan, Vlad; Buettener, Michael; Navda, Vishnu; Ramjee, Ramachandran; Yerramalli, Srinivas (NSDI, 2012)
The quest for higher data rates in WiFi is leading to the development of standards that make use of wide channels (e.g., 40MHz in 802.11n and 80MHz in 802.11ac). In this paper, we argue against this trend of using wider channels, and instead advocate that radios should communicate over multiple narrow channels for efficient and fair spectrum utilization. We propose WiFi-NC, a novel PHY-MAC design that allows radios to use WiFi over multiple narrow channels simultaneously. To enable WiFi-NC, we have developed the compound radio, a single wideband radio that exposes the abstraction of multiple narrow channel radios, each with independent transmission, reception and carrier sensing capabilities. The architecture of WiFi-NC makes it especially suitable for use in whitespaces where free spectrum may be fragmented. Thus, we also develop a frequency band selection algorithm for WiFi-NC making it suitable for use in whitespaces. WiFi-NC has been implemented on an FPGA-based software defined radio platform. Through real experiments and simulations, we demonstrate that WiFi-NC provides better efficiency and fairness in both common WiFi as well as future whitespace scenarios.